Efeitos da sentença na incidência e exigibilidade das astreintes - Alves, Roberta Rodrigues (2014)
This monograph has as its objective the analysis of the use of the "astreintes" in Brazilian's civil procedure law, in order to verify the solutions found by the doctrine and jurisprudence in situations of cases won after the setting of the fine. This way, addresses the origin of coercive measures in civil procedure law, and, by consequence, a evolutionary research until present day. Therefore, analyses its fields of uses according to the Brazilian civil procedure law. After, analyses the particularities of the institute according to the current legislative system and the present writing of the law project that aims the creation of a new Civil Procedure Code. At last, the effects of the merit sentence are analyzed in more depth in the occurrence and chargeability of the "astreintes", according to the Brazilian doctrine and jurisprudence